Nursing Staff's Observations of BPSD Amongst Older Adults with Dementia Living in a Nursing Home: A Qualitative Study - Emerentia Grootscholten; Irina Poslawsky; Ton Bakker (MDPI AG, 2023)
The majority of older adults with dementia living in a nursing home exhibit behavioral and psychological symptoms of dementia (BPSD). This behavior is difficult for residents to cope with. Early recognition of BPSD is important in order to implement personalized integrated treatment, and nursing staff are in the unique position to consistently observe residents' behavior. The aim of this study was to explore nursing staff's experiences observing BPSD of nursing home residents with dementia. A generic qualitative design was chosen. Twelve semi-structured interviews were conducted with nursing staff members until data saturation. Data were analyzed using inductive thematic analysis. Four themes were identified: "group harmony" observations from a group perspective, focused on the disturbance of group harmony; an "intuitive approach", which involves observing unconsciously and without a set method; "reactive intervention", which refers to immediate removal of observed triggers without exploring the causes of behaviors; and "sharing information", which is delayed sharing of observed behavior with other disciplines. The current way in which nursing staff observe BPSD and share observations within the multidisciplinary team explain several existing barriers to achieving high treatment fidelity for BPSD with personalized integrated treatment. Therefore, nursing staff must be educated to structure their daily observations methodologically and interprofessional collaboration improved to share their information in a timely manner.